2023
DOI: 10.3389/fneur.2023.1121026
|View full text |Cite
|
Sign up to set email alerts
|

Research progress in extracorporeal shock wave therapy for upper limb spasticity after stroke

Abstract: Spasticity is one of the most common complications after stroke. With the gradual intensification of spasticity, stroke patients will have a series of problems such as joint ankylosis and movement restriction, which affect the daily activities and increase the burden on patients' families, medical staff and society. There are many ways to treat post-stroke spasticity before, including physical therapy and exercise therapy, drug therapy, surgery and so on, but not satisfied because of a few shortcomings. In rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 92 publications
(89 reference statements)
0
12
0
Order By: Relevance
“…Highlighted details: In recent years, clinical studies have demonstrated that ESWT can be used to treat spasticity after a stroke. Duan et al [ 31 ] compiled potential ESWT mechanisms of interest. First, ESWT stimulates the production of nitric oxide, following which it reduces the level of acetylcholine at the neuromuscular junction, thereby alleviating muscle spasms.…”
Section: Resultsmentioning
confidence: 99%
“…Highlighted details: In recent years, clinical studies have demonstrated that ESWT can be used to treat spasticity after a stroke. Duan et al [ 31 ] compiled potential ESWT mechanisms of interest. First, ESWT stimulates the production of nitric oxide, following which it reduces the level of acetylcholine at the neuromuscular junction, thereby alleviating muscle spasms.…”
Section: Resultsmentioning
confidence: 99%
“…The results of our study showed that there was no statistically signi cant difference in the effect of low vs. medium rESWT on forearm spasticity of the upper limbs, which may be due to several reasons. First, rESWT spreads around in the form of divergence, with a wide range of energy involved, and the energy decreases with increasing propagation distance [23]. However, the forearm muscles are numerous and slender, and the super cial muscles are palpable on the body surface [24], while the lower EFD can penetrate the deep muscles.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of ESWT on spasticity are thought to involve multiple mechanisms, including nitric oxide production, rheological property changes, motor neuron excitability reduction, and induction of neuromuscular transmission dysfunction ( 6 8 , 16 , 21 ).…”
Section: Eswt For Muscle Spasticity and Sensitization Theorymentioning
confidence: 99%
“…This effect may disrupt the functional link between actin and myosin, causing the connective tissue within the spastic muscle to loosen. ESWT may also cause vasodilation via enzymatic and non-enzymatic nitric oxide synthesis, increasing blood flow to the area and influencing the secretion of interleukins involved in inflammation and growth factor activation ( 6 8 , 16 , 21 ).…”
Section: Eswt For Muscle Spasticity and Sensitization Theorymentioning
confidence: 99%